Effect of astaxanthin-enriched virgin coconut oil concentration on lip balm properties and sun protector factor (SPF) activity - Prayitno, Dwi Imam; Rahmalia, Winda; Herlina, Elisabet (Jurnal Ilmiah Farmasi, 2026)
Background: Our previous research successfully extracted astaxanthin from fermented Acetes shrimp (cincalok) using virgin coconut oil (VCO), resulting in astaxanthin-enriched VCO (VCOA). This innovative approach demonstrates the feasibility of incorporating VCOA into cosmetic preparations. In particular, its application in lip balm formulationsObjective: This study aimed to formulate a lip balm incorporating VCOA in combination with tengkawang butter.Method: The physical properties and sunscreen activity of the lip balm were evaluated as a function of storage duration at room temperature. The study examined the influence of varying concentrations and compositions of astaxanthin-enriched virgin coconut oil (VCOA) and illipe fat on the formulation. Key parameters assessed included homogeneity, pH stability, color stability, and melting point.Results: The test results indicated that a homogeneous lip balm was obtained when a high concentration of VCOA (15-30% w/w) was used and was stable for 28 days of storage. The acidity level (pH: 4.56-6.69) and melting point of the lip balm (50–67°C) have met the Indonesian National Standard. The presence of VCOA causes the lip balm to be yellow to orange. The resulting lip balm shows a sun protection factor (SPF: 51.1674 ± 0.0364) value with an ultra-protection category.Conclusion: In this study, astaxanthin was extracted from cincalok using VCO to produce VCOA, which was directly applied as a lip balm ingredient. The application of VCOA at the highest concentration (30%) yielded lip balm with excellent homogeneity, stable pH and melting point in accordance with SNI standards, the most pronounced color, and the highest SPF value.